2017
DOI: 10.1039/c6ra28100a
|View full text |Cite
|
Sign up to set email alerts
|

Non-ionic self-assembling amphiphilic polyester dendrimers as new drug delivery excipients

Abstract: Solubility enhancement of poorly soluble antibiotics via self-assembling nano systems could be a promising approach to effectively treat bacterial infections in the current scenario of evolving resistant species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…NMEO displayed a cell viability between 79.42 to 88.12%, 78.42 to 81.75% and 76.96 to 79.70% for A549, HEK-293 and HEP G2 cells respectively (Figure 3.2). The results displayed no dose dependent trends and is consistent with previous studies that report on materials that exhibit cell viability that is independent of the concentration (Romic et al, 2016;Di Gioia et al, 2015;Sikwal et al, 2017).…”
Section: In Vitro Cytotoxicitysupporting
confidence: 91%
“…NMEO displayed a cell viability between 79.42 to 88.12%, 78.42 to 81.75% and 76.96 to 79.70% for A549, HEK-293 and HEP G2 cells respectively (Figure 3.2). The results displayed no dose dependent trends and is consistent with previous studies that report on materials that exhibit cell viability that is independent of the concentration (Romic et al, 2016;Di Gioia et al, 2015;Sikwal et al, 2017).…”
Section: In Vitro Cytotoxicitysupporting
confidence: 91%
“…Considering various possible structures among gemini amphiphiles, the nonionic one is advantageous for the drug delivery applications due to reduced cytotoxicity. [43][44][45] Furthermore, the presence of two hydrophobic alkyl tails in gemini amphiphiles allow sharp and uniform decrease in CAC value than their monomeric counterparts and thus making a valuable contribution for therapeutic applications. Nonionic gemini amphiphiles based on carbohydrates are known in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Despite FA being an effective agent against Gram-positive bacteria, there has been only one report for enhancing its solubility and activity using nanomicelles, which further involved the use of a newly synthesized material, i.e., polyester dendrimers. 40 A nano precipitation antisolvent technique, which was used to formulate nanosuspensions, has been shown to have advantages, such as little energy input, readily available machinery, and easy scale-up. It also allows for the preparation of nanosuspensions without the use of additional specialized materials, like the study reported by Sikwal et al 40 Development of pharmaceutical dosage forms requires an understanding of the in vitro and in vivo performance of the dosage forms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…40 A nano precipitation antisolvent technique, which was used to formulate nanosuspensions, has been shown to have advantages, such as little energy input, readily available machinery, and easy scale-up. It also allows for the preparation of nanosuspensions without the use of additional specialized materials, like the study reported by Sikwal et al 40 Development of pharmaceutical dosage forms requires an understanding of the in vitro and in vivo performance of the dosage forms. In vitro studies have been shown to be convenient as they (a) reduce costs, (b) provide an opportunity to more directly assess product performance, and (c) offer benefits in terms of ethical considerations.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation